Predicting Occupational Injury Causal Factors Using Text-based Analytics: A Systematic Review - Mohamed Zul Fadhli Khairuddin; Khairunnisa Hasikin; Nasrul Anuar Abd Razak; Khin Wee Lai; Mohd Zamri Osman; Muhammet Fatih Aslan; Kadir Sabanci; Suresh Chandra Satapathy; Xiang Wu; Muhammad Mokhzaini Azizan (FRONTIERS, 2024)
Indexed by WOS/Scopus/ERA